Metal ceramic hard wear-resistant coating material and preparation method thereof
The cermet coating is prepared by using NiCoCr medium-entropy alloy powder and HVAF thermal spraying technology doped with Ti-O elements and laser impact treatment, which solves the problem of softening and deformation of existing coatings under high temperature and large loads, and achieves higher wear resistance and high temperature resistance.
Patent Information
- Application Number
- CN202411882843.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-04
AI Technical Summary
The existing cermet coatings are prone to softening and deformation under high temperature and high load conditions, resulting in insufficient wear resistance and even damage or peeling.
The NiCoCr medium-entropy alloy powder doped with Ti-O elements was used to prepare a cermet coating through HVAF thermal spraying technology, and laser impact treatment was carried out to control the precipitation of chemical short-range ordered nanophase to strengthen the bonding phase, and finally obtain a cermet hard wear-resistant coating with the NiCoCr-Ti-O medium-entropy alloy with the FCC structure as the bonding phase.
It improves the wear resistance and high temperature resistance of the coating, enhances the strength and toughness of the bonded phase, and improves the overall performance of the coating.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention relates to a coating material and a preparation method thereof, in particular to a metal ceramic hard wear-resistant coating material and a preparation method thereof, belonging to the fields of new materials, advanced manufacturing and surface engineering. Background Art
[0002] In the fields of advanced manufacturing such as steam turbines and gas turbines, as well as petrochemicals, coal chemicals, polysilicon, and new energy, various key components are easily affected by high temperatures, hard particles, and corrosive media, and are prone to failures such as oxidation, wear, and corrosion. At present, through surface treatment, various coatings can be formed to ensure the safe and stable operation of equipment and increase the service life of parts.
[0003] CN101148747A discloses a thermal spray WC / Co powder and coating, the powder contains 5-25% cobalt, 5-6% carbon, and tungsten as the balance, and has a spherical particle structure, a particle size of ≤150μm, and a main body of 15-90μm. The preparation of the powder includes the following steps: 1) screening, cleaning, and drying pure tungsten powder; 2) spheroidizing tungsten powder; 3) carbonizing spherical tungsten powder; 4) cobalt coating spherical tungsten carbide. The coating prepared by supersonic flame spraying using cobalt tungsten carbide powder has a dense and uniform structure, is closely bonded to the substrate, and has a porosity of less than 1%. CN111118436A discloses a Co-based WC / TiN / TiCN composite coating, comprising a metal substrate, a Co-based WC coating, a TiN gradient coating and a TiCN gradient coating sequentially deposited on the metal substrate; the Co-based WC composite coating is prepared by supersonic flame spraying of Co-based alloy powder and WC powder, and the TiN gradient coating and the TiCN gradient coating are prepared by ion-assisted unbalanced magnetron sputtering technology.
[0004] Although existing metal-ceramic coatings have excellent performance, the hardness of the metal phase is lower than that of the ceramic phase, and it is easy to soften and deform under high temperature and high load conditions, resulting in insufficient wear resistance of the coating, and even damage or peeling. Therefore, it is urgent to strengthen the metal-ceramic coating to improve its performance. Summary of the invention
[0005] The present invention aims to provide a metal ceramic hard wear-resistant coating material and a preparation method thereof, which meet the requirements of improving coating performance. The present invention proposes to prepare a composite metal ceramic powder based on the preparation of NiCoCr medium entropy alloy powder doped with Ti-O elements, prepare a thermal spray coating by HVAF, perform laser shock treatment, and control the precipitation of chemical short-range ordered nanophase to strengthen the bonding phase, and finally obtain a metal ceramic hard wear-resistant coating with FCC structure NiCoCr-Ti-O medium entropy alloy as the bonding phase.
[0006] The metal ceramic hard wear-resistant coating material of the present invention is characterized in that its components are WC and a medium entropy alloy of NiCoCr doped with Ti-O in an equal molar ratio, and the weight ratio of the two is (80-90):(5-15); in the medium entropy alloy of NiCoCr doped with Ti-O in an equal molar ratio, the molar ratio of Ni:Ti is 1:(0.05-0.1); the physical phase composition of the metal ceramic hard wear-resistant coating material is WC of HCP structure+NiCoCr-Ti-O of FCC structure+TiO2 of rutile structure+W2C of HCP structure, an L12 chemical short-range ordered coherent nanophase with a size of 1-10 nm is precipitated in the NiCoCr-Ti-O phase, and the O element is located in the octahedral gap of the FCC structure.
[0007] The method for preparing the metal ceramic hard wear-resistant coating material of the present invention is characterized by comprising the following steps in sequence: (1) Preparation of NiCoCr medium-entropy alloy powder doped with Ti-O element: First, TiCl4 is used as a precursor and Ti(OH)4 sol is prepared by a sol-gel method; then, Ni, Co, and Cr powders are weighed in a molar ratio of 1:1:1, ball-milled in a planetary ball mill for 56-72 hours, and filtered to obtain NiCoCr medium-entropy alloy slurry; then, the NiCoCr medium-entropy alloy slurry is mixed with Ti(OH)4 sol to control the molar ratio of Ni:Ti to 1:(0.05-0.1), Tween 80 is added, and after ultrasonic dispersion and pH adjustment, a slurry with a Zeta potential of 30-35 mV is formed; spray drying is performed, and the obtained powder is sintered at 1250-1300°C for 1-2 hours in an Ar atmosphere of 2-5 MPa, and a NiCoCr medium-entropy alloy powder doped with Ti-O element with a particle size of 5-10 μm is prepared after crushing and sieving; (2) Preparation of metal ceramic powder: Weigh WC powder and NiCoCr medium entropy alloy powder doped with Ti-O element in a weight ratio of (80-90): (5-15), mix by ball milling for 8-12 hours, filter, spray dry, and then keep at 1100-1200℃ for 1-2 hours to prepare metal ceramic powder with a phase composition of WC+FCC structure of NiCoCr-Ti-O of HCP structure; (3) Preparation of metal ceramic coating by HVAF: The prepared metal ceramic powder is used as feed material to prepare the metal ceramic coating on the high temperature alloy substrate by HVAF. TiO2 and W2C are formed during the spraying process. The phase composition of the coating is WC with HCP structure + NiCoCr-Ti-O with FCC structure + TiO2 with rutile structure + W2C with HCP structure. (4) Laser shock treatment of coating: Pulsed laser was used to perform laser shock treatment on the metal ceramic coating. First, a 0.1 mm thick black tape was pasted on the surface of the prepared metal ceramic coating as an absorption layer. Deionized water was used to form a 1-3 mm water curtain on the surface of the black tape as a constraint layer. The high-energy plasma generated by laser shock was used to cause plastic deformation of the coating. The dislocation density in the coating increased from (1-5) × 10 7 mm -2 Increase to (4~9)×10 8 mm -2 , the phase composition of the coating does not change; (5) Precipitation of chemical short-range ordered phase in the coating: The laser shock treated coating was heated to 1100-1150°C in a vacuum, kept at this temperature for 1-3 h to complete the solid solution, and then filled with argon gas to cool to below 100°C; then heated to 750-800°C, kept at this temperature for 2-4 h, and then cooled in the furnace. In the metal ceramic coating, a L12 chemical short-range ordered coherent nanophase with a size of 1-10 nm was precipitated in the FCC structure NiCoCr-Ti-O phase. The O element was located in the octahedral gap of the FCC structure. The dislocation density in the coating was 5×10 7 mm -2 ~1×10 8 mm -2 .
[0008] The preparation method of the metal ceramic hard wear-resistant coating material of the present invention is further characterized by: (1) When preparing Ti-O-doped NiCoCr medium-entropy alloy powder, first mix anhydrous ethanol and deionized water in a volume ratio of 1:1, add HCl until the pH value is 3~4, and form solution A after magnetic stirring; TiCl4 and anhydrous ethanol are mixed in a volume ratio of 1:(3~5), and form solution B after magnetic stirring; measure liquid A and liquid B in a volume ratio of 1:(2~3), add liquid B to liquid A at room temperature, and form Ti(OH)4 sol by magnetic stirring; after mixing the NiCoCr medium-entropy alloy slurry and Ti(OH)4 sol, add Tween 80 in an amount of 1~2% of the weight of the NiCoCr medium-entropy alloy powder, ultrasonically disperse for 15~40 minutes, and adjust the pH to 8~9 with ammonia water; (2) When preparing metal ceramic powder, the ball mill speed is 150~250r / min, WC-8Co carbide grinding balls with a diameter of 6mm are used, the ball milling medium is anhydrous ethanol, the weight ratio of grinding balls: powder: anhydrous ethanol during ball milling is 5:1:2, and a 400-mesh screen is used for filtration after ball milling. During spray drying, the atomizing disk speed is 6000~6500r / min, and the drying temperature is 120~130℃; (3) When HVAF is used to prepare metal ceramic coatings, the air pressure is 0.6~0.8MPa, the propane pressure is 0.6~0.9MPa, the powder feeding rate is 6~8kg / h, and the spraying distance is 200~250mm; (4) During the laser shock treatment of the coating, the laser wavelength is 1.053 μm, the laser spot diameter is 3-4 mm, the spot overlap rate is 50%, the pulse energy is 8-9 J, and the pulse width is 15-20 ns; (5) The heating rate during the precipitation of the chemical short-range ordered phase in the coating is 1~5℃ / min, and the initial vacuum degree is 0.1~1Pa.
[0009] The advantages of the present invention are: (1) the FCC structure of NiCoCr medium entropy alloy is introduced as the bonding phase of the metal ceramic coating. Compared with the traditional Co-based or Ni-based bonding phase, the toughness of the bonding phase is enhanced; (2) the nanophase precipitated in the high entropy alloy bonding phase and the W2C formed by spraying have a high strengthening effect on the bonding phase, thereby improving the wear resistance. (3) The interstitial oxygen atoms in the coating strengthen the NiCoCr medium entropy alloy. (4) No other intermetallic compound phase is generated in the metal ceramic with the medium entropy alloy as the bonding phase, and the performance of the coating will not be deteriorated. (5) The formed TiO2 can reduce the friction coefficient and improve the wear resistance of the coating. (6) The medium entropy alloy bonding phase and the precipitated phase improve the wear resistance and high temperature resistance of the metal ceramic hard coating of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Schematic diagram of the preparation method of the metal ceramic hard wear-resistant coating material of the present invention. DETAILED DESCRIPTION
[0011] Example 1: The composition of the metal ceramic hard wear-resistant coating material is WC and NiCoCr medium entropy alloy doped with Ti-O in equal molar ratio, and the weight ratio of the two is 80:7; in the NiCoCr medium entropy alloy doped with Ti-O in equal molar ratio, the molar ratio of Ni:Ti is 1:0.05; the phase composition of the metal ceramic hard wear-resistant coating material is WC with HCP structure + NiCoCr-Ti-O with FCC structure + rutile TiO2 with HCP structure W2C, and L12 chemical short-range ordered coherent nanophase with a size of 3 nm is precipitated in the NiCoCr-Ti-O phase, and the O element is located in the octahedral gap of the FCC structure.
[0012] Prepare the metal ceramic hard wear-resistant coating material according to the following steps: (1) Preparation of Ti-O-doped NiCoCr medium-entropy alloy powder: First, TiCl4 was used as a precursor and a sol-gel method was used to prepare a Ti(OH)4 sol. Anhydrous ethanol and deionized water were mixed in a volume ratio of 1:1, and HCl was added dropwise until the pH value was 3. Solution A was formed after magnetic stirring. TiCl4 and anhydrous ethanol were mixed in a volume ratio of 1:2, and solution B was formed after magnetic stirring. Solution A and solution B were measured in a volume ratio of 1:2, and solution B was added dropwise to solution A at room temperature. Ti(OH)4 sol was formed after magnetic stirring. Then, solution A and solution B were weighed in a molar ratio of 1:1:1. Ni, Co and Cr powders were ball-milled in a planetary ball mill for 56 hours, and then filtered to obtain a NiCoCr medium-entropy alloy slurry; the NiCoCr medium-entropy alloy slurry was then mixed with Ti(OH)4 sol, and the molar ratio of Ni:Ti was controlled to be 1:0.05. After the NiCoCr medium-entropy alloy slurry and Ti(OH)4 sol were mixed, Tween 80 was added in an amount of 1% of the weight of the NiCoCr medium-entropy alloy powder, and ultrasonic dispersion treatment was performed for 15 minutes. The pH was adjusted to 8 with ammonia water to form a slurry with a Zeta potential of 31 mV; spray drying was performed, and the obtained powder was sintered at 1250°C in an Ar atmosphere of 2 MPa for 1 hour, and a NiCoCr medium-entropy alloy powder doped with Ti-O elements with a particle size of 6 μm was prepared after crushing and sieving; (2) Preparation of metal ceramic powder: WC powder and NiCoCr medium entropy alloy powder doped with Ti-O element were weighed in a weight ratio of 80:7 and mixed by ball milling for 8 hours. The ball mill speed was 180 r / min. WC-8Co carbide grinding balls with a diameter of 6 mm were used. The ball milling medium was anhydrous ethanol. The weight ratio of grinding balls: powder: anhydrous ethanol during ball milling was 5:1:2. After ball milling, a 400-mesh sieve was used for filtration. The atomizing disk speed during spray drying was 6000 r / min, the drying temperature was 120°C, and then the powder was kept at 1100°C for 1 hour to prepare NiCoCr-Ti-O metal ceramic powder with a phase composition of HCP structure WC+FCC structure; (3) Preparation of metal ceramic coating by HVAF: The prepared metal ceramic powder was used as feed material to prepare the metal ceramic coating on the high temperature alloy substrate by HVAF. The air pressure was 0.6 MPa, the propane pressure was 0.7 MPa, the powder feeding rate was 6 kg / h, and the spraying distance was 200 mm. TiO2 and W2C were formed during the spraying process. The phase composition of the coating was WC with HCP structure + NiCoCr-Ti-O with FCC structure + TiO2 with rutile structure + W2C with HCP structure. (4) Laser shock treatment of coating: Pulsed laser was used to perform laser shock treatment on the metal ceramic coating. First, a 0.1 mm thick black tape was pasted on the surface of the prepared metal ceramic coating as an absorption layer. Deionized water was used to form a 1 mm water curtain on the surface of the black tape as a constraint layer. The laser wavelength was 1.053 μm, the laser spot diameter was 3 mm, the spot overlap rate was 50%, the pulse energy was 8 J, and the pulse width was 15 ns. The high-energy plasma generated by the laser shock was used to cause plastic deformation of the coating. The dislocation density in the coating increased from 2.2 × 10 7 mm -2 Increased to 5.3×10 8 mm -2 , the phase composition of the coating does not change; (5) Precipitation of chemical short-range ordered phase in the coating: The laser shock treated coating was heated to 1100°C in vacuum at a heating rate of 1°C / min and an initial vacuum of 0.1 Pa. The coating was kept at this temperature for 1 h to complete the solid solution reaction, and then filled with argon gas to cool to below 100°C. The coating was then heated to 750°C, kept at this temperature for 2 h, and then cooled in the furnace. A 3 nm L12 chemical short-range ordered coherent nanophase was precipitated in the FCC structure NiCoCr-Ti-O phase in the metal ceramic coating. The O element was located in the octahedral gap of the FCC structure. The dislocation density in the coating was 7.1×10 7 mm -2 .
[0013] Example 2: The composition of the metal ceramic hard wear-resistant coating material is WC and NiCoCr medium entropy alloy doped with Ti-O in equal molar ratio, and the weight ratio of the two is 85:9; in the NiCoCr medium entropy alloy doped with Ti-O in equal molar ratio, the molar ratio of Ni:Ti is 1:0.9; the phase composition of the metal ceramic hard wear-resistant coating material is WC with HCP structure + NiCoCr-Ti-O with FCC structure + TiO2 with rutile structure + W2C with HCP structure, and L12 chemical short-range ordered coherent nanophase with a size of 7 nm is precipitated in the NiCoCr-Ti-O phase, and the O element is located in the octahedral gap of the FCC structure.
[0014] Prepare the metal ceramic hard wear-resistant coating material according to the following steps: (1) Preparation of Ti-O-doped NiCoCr medium-entropy alloy powder: Ti(OH)4 sol was prepared by sol-gel method using TiCl4 as precursor, anhydrous ethanol and deionized water were mixed in a volume ratio of 1:1, HCl was added dropwise until the pH value was 4, and solution A was formed by magnetic stirring; TiCl4 and anhydrous ethanol were mixed in a volume ratio of 1:5, and solution B was formed by magnetic stirring; solution A and solution B were measured in a volume ratio of 1:3, and solution B was added dropwise to solution A at room temperature, and solution B was formed by magnetic stirring. to form Ti(OH)4 sol; then weigh Ni, Co and Cr powders in a molar ratio of 1:1:1, ball mill in a planetary ball mill for 70 hours, and obtain NiCoCr medium entropy alloy slurry after filtering; then mix the NiCoCr medium entropy alloy slurry with Ti(OH)4 sol, control the molar ratio of Ni:Ti to be 1:0.9, add Tween 80 in an amount of 2% of the weight of the NiCoCr medium entropy alloy powder after mixing the NiCoCr medium entropy alloy slurry with Ti(OH)4 sol, ultrasonically disperse for 40 min, adjust the pH to 9 with ammonia water, and form a slurry with a Zeta potential of 34 mV; spray dry, and sinter the obtained powder at 1300°C in an Ar atmosphere of 4MPa for 2h, and prepare a NiCoCr medium entropy alloy powder doped with Ti-O element with a particle size of 8 μm after crushing and sieving; (2) Preparation of metal ceramic powder: WC powder and NiCoCr medium entropy alloy powder doped with Ti-O element were weighed in a weight ratio of 85:9 and mixed by ball milling for 12 hours. The ball mill speed was 240 r / min. WC-8Co carbide grinding balls with a diameter of 6 mm were used. The ball milling medium was anhydrous ethanol. The weight ratio of grinding balls: powder: anhydrous ethanol during ball milling was 5:1:2. After ball milling, a 400-mesh sieve was used for filtration. The atomizing disk speed during spray drying was 6500 r / min, the drying temperature was 125°C, and then the powder was kept at 1200°C for 1.5 hours to prepare NiCoCr-Ti-O metal ceramic powder with a phase composition of HCP structure WC+FCC structure; (3) Preparation of metal ceramic coating by HVAF: The prepared metal ceramic powder was used as feed material to prepare the metal ceramic coating on the high temperature alloy substrate by HVAF, with the air pressure of 0.8 MPa, the propane pressure of 0.8 MPa, the powder feeding rate of 8 kg / h, and the spraying distance of 240 mm. TiO2 and W2C were formed during the spraying process, and the phase composition of the coating was WC with HCP structure + NiCoCr-Ti-O with FCC structure + TiO2 with rutile structure + W2C with HCP structure. (4) Laser shock treatment of coating: Pulsed laser was used to perform laser shock treatment on the metal ceramic coating. First, a 0.1 mm thick black tape was pasted on the surface of the prepared metal ceramic coating as an absorption layer. Deionized water was used to form a 2 mm water curtain on the surface of the black tape as a constraint layer. The laser wavelength was 1.053 μm, the laser spot diameter was 4 mm, the spot overlap rate was 50%, the pulse energy was 9 J, and the pulse width was 20 ns. The high-energy plasma generated by the laser shock caused the coating to undergo plastic deformation. The dislocation density in the coating increased from 3.4 × 10 7 mm -2 Increased to 8.1×10 8 mm -2 , the phase composition of the coating does not change; (5) Precipitation of chemical short-range ordered phase in the coating: The laser shock treated coating was heated to 1150°C in vacuum at a heating rate of 4°C / min and an initial vacuum of 0.5 Pa. The coating was kept at this temperature for 2 h to complete the solid solution reaction, and then filled with argon gas to cool to below 100°C. The coating was then heated to 800°C, kept at this temperature for 4 h, and then cooled in the furnace. A 7 nm L12 chemical short-range ordered coherent nanophase was precipitated in the FCC structure NiCoCr-Ti-O phase in the metal ceramic coating. The O element was located in the octahedral gap of the FCC structure. The dislocation density in the coating was 8.9×10 7 mm -2 .
Claims
1. A metal ceramic hard wear-resistant coating material, characterized in that Its composition is WC and NiCoCr medium entropy alloy doped with Ti-O in equal molar ratio, and the weight ratio of the two is (80~90):(5~15); in the NiCoCr medium entropy alloy doped with Ti-O in equal molar ratio, the molar ratio of Ni:Ti is 1:(0.05~0.1); the phase composition of the metal ceramic hard wear-resistant coating material is WC with HCP structure + NiCoCr-Ti-O with FCC structure + TiO2 with rutile structure + W2C with HCP structure, and L12 chemical short-range ordered coherent nanophase with a size of 1~10nm is precipitated in the NiCoCr-Ti-O phase, and the O element is located in the octahedral gap of the FCC structure.
2. A method for preparing a metal ceramic hard wear-resistant coating material, characterized in that The following steps are included in sequence: (1) Preparation of Ti-O-doped NiCoCr medium-entropy alloy powder: First, TiCl4 is used as a precursor and Ti(OH)4 sol is prepared by a sol-gel method; then, Ni, Co, and Cr powders are weighed in a molar ratio of 1:1:1, ball-milled in a planetary ball mill for 56-72 hours, and filtered to obtain a NiCoCr medium-entropy alloy slurry; then, the NiCoCr medium-entropy alloy slurry is mixed with the Ti(OH)4 sol to control the molar ratio of Ni:Ti to be 1:(0.05-0.1), Tween 80 is added, and after ultrasonic dispersion and pH adjustment, a slurry with a Zeta potential of 30-35 mV is formed; spray drying is performed, and the obtained powder is sintered at 1250-1300°C for 1-2 hours in an Ar atmosphere of 2-5 MPa, and a NiCoCr medium-entropy alloy powder doped with Ti-O elements with a particle size of 5-10 μm is prepared after crushing and sieving; (2) Preparation of metal ceramic powder: Weigh WC powder and NiCoCr medium entropy alloy powder doped with Ti-O element in a weight ratio of (80-90): (5-15), mix by ball milling for 8-12 hours, filter, spray dry, and then keep at 1100-1200℃ for 1-2 hours to prepare metal ceramic powder with a phase composition of WC+FCC structure of HCP structure NiCoCr-Ti-O; (3) Preparation of metal ceramic coating by HVAF: The prepared metal ceramic powder is used as feed material to prepare the metal ceramic coating on the high temperature alloy substrate by HVAF. TiO2 and W2C are formed during the spraying process. The phase composition of the coating is WC with HCP structure + NiCoCr-Ti-O with FCC structure + TiO2 with rutile structure + W2C with HCP structure. (4) Laser shock treatment of coating: Pulsed laser was used to perform laser shock treatment on the metal ceramic coating. First, a 0.1 mm thick black tape was pasted on the surface of the prepared metal ceramic coating as an absorption layer. Deionized water was used to form a 1-3 mm water curtain on the surface of the black tape as a constraint layer. The high-energy plasma generated by laser shock was used to cause plastic deformation of the coating. The dislocation density in the coating increased from (1-5) × 10 7 mm -2 Increase to (4~9)×10 8 mm -2 , the phase composition of the coating does not change; (5) Precipitation of chemical short-range ordered phase in the coating: The laser shock treated coating was heated to 1100-1150°C in a vacuum, kept at this temperature for 1-3 h to complete the solid solution, and then filled with argon gas to cool to below 100°C; then heated to 750-800°C, kept at this temperature for 2-4 h, and then cooled in the furnace. In the metal ceramic coating, a L12 chemical short-range ordered coherent nanophase with a size of 1-10 nm was precipitated in the FCC structure NiCoCr-Ti-O phase. The O element was located in the octahedral gap of the FCC structure. The dislocation density in the coating was 5×10 7 mm -2 ~1×10 8 mm -2 .
3. The method for preparing the metal ceramic hard wear-resistant coating material according to claim 2, further characterized in that: (1) When preparing Ti-O-doped NiCoCr medium-entropy alloy powder, first mix anhydrous ethanol and deionized water in a volume ratio of 1:1, add HCl until the pH value is 3~4, and form solution A after magnetic stirring; TiCl4 and anhydrous ethanol are mixed in a volume ratio of 1:(3~5), and form solution B after magnetic stirring; measure liquid A and liquid B in a volume ratio of 1:(2~3), add liquid B to liquid A at room temperature, and form Ti(OH)4 sol by magnetic stirring; after mixing the NiCoCr medium-entropy alloy slurry and Ti(OH)4 sol, add Tween 80 in an amount of 1~2% of the weight of the NiCoCr medium-entropy alloy powder, ultrasonically disperse for 15~40 minutes, and adjust the pH to 8~9 with ammonia water; (2) When preparing metal ceramic powder, the ball mill speed is 150~250r / min, WC-8Co carbide grinding balls with a diameter of 6mm are used, the ball milling medium is anhydrous ethanol, the weight ratio of grinding balls: powder: anhydrous ethanol during ball milling is 5:1:2, and a 400-mesh screen is used for filtration after ball milling. During spray drying, the atomizing disk speed is 6000~6500r / min, and the drying temperature is 120~130℃; (3) When HVAF is used to prepare metal ceramic coatings, the air pressure is 0.6~0.8MPa, the propane pressure is 0.6~0.9MPa, the powder feeding rate is 6~8kg / h, and the spraying distance is 200~250mm; (4) During the laser shock treatment of the coating, the laser wavelength is 1.053 μm, the laser spot diameter is 3-4 mm, the spot overlap rate is 50%, the pulse energy is 8-9 J, and the pulse width is 15-20 ns; (5) The heating rate during the precipitation of the chemical short-range ordered phase in the coating is 1~5℃ / min, and the initial vacuum degree is 0.1~1Pa.
Citation Information
Patent Citations
Hot spraying WC / Co powder and coat preparation
CN101148747A
Co base-WC / TiN / TiCN composite coating, and repairing method for cold stamping mould
CN111118436A